Humidtropics in the Central Mekong Action Area - Hiwasaki, L. (World Agroforestry Centre, 2016)
This chapter introduces Humidtropics, the CGIAR Research Program (CRP) on Integrated Systems for the Humid Tropics, and the research for development (R4D) activities implemented from 2013 to 2016 in the Central Mekong Action Area. The chapter also provides an overview of the other book chapters.